Case reportRecanalization of chronic total coronary artery occlusions – the role of multi-slice computed tomography. Case report - Bryniarski, Leszek; Dąbrowski, Maciej; Surowiec, Sławomir; Witkowski, Adam; Pręgowski, Jerzy; Kawecka-Jaszcz, Kalina (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Non-invasive diagnostics of the heart allow one to assess myocardium viability (indication for procedure) and facilitate the choice of strategy and tools used during percutaneous coronary intervention (PCI). We present a case of PCI of chronic total occlusion (CTO) after non-invasive diagnostics, including multi-slice computed tomography (MSCT).